APPROPRIATENESS OF FRESH FROZEN PLASMA TRANSFUSION-A RETROSPECTIVE ANALYSIS - M., MANIMOZHI; M., PARIMALAM; J., RAVISHANKAR (International Journal of Current Pharmaceutical Research, 2026)
Objective: Every blood component carries inherent risk of adverse transfusion reactions and transfusion-transmitted infections (TTI). As Fresh frozen plasma (FFP) is one of the commonly used blood components, appropriate and rational use is necessary for patient safety. The objective of the study was to evaluate the appropriateness of FFP utilization in clinical practice. Methods: This retrospective study was conducted at the Department of Immunohematology and Blood Transfusion, Tirunelveli Medical College and Hospital, Tirunelveli, Tamilnadu, India in June, 2024. Blood Request Forms with request for FFP transfusion between December 2023 and May 2024 were analysed. Data entry and statistical analysis was performed using Microsoft Excel sheet. Results: 631 patients received 1798 FFP units (mean=2.85 units), 16.1% of transfusions were in the age group of 31-40 years (n=291/1798), 53.6% were in males (n=963/1798), 27.5% were issued to the Department of General medicine (n=495/1798). 65.1% of transfusions were appropriate (n=1171/1798), the most common indication being therapeutic plasma exchange. Inappropriate transfusion indications were for volume replacement, to improve wound healing and prophylactic use during surgeries. Conclusion: As FFP is involved more in adverse transfusion reactions like allergy and Transfusion-related acute lung injury (TRALI), inappropriate indications can be reduced significantly with continuous education of end users by regular CMEs, interactive sessions, discussion in Hospital transfusion committee and prospective audits, to ensure optimal use of the scarce resource and to reduce transfusion-related adverse events.